Food safety knowledge, beliefs and behaviour among health sciences-related field undergraduate students at a local university - Nur Aisyah Zailani; Nurul Shafikah Idris; Ahmad Mujahid Zainal; Umi Haniq Mohamad Kamil; Mohamed Rafiq Mohd Radhuan; Syed Alif Irfan Syed Ahmad Jaafar; Muhammad Ikram A. Wahab; Siti Shahara Zulfakar (Penerbit Universiti Kebangsaan Malaysia, 2022)
Foodborne disease is among the primary illness that causes morbidity and mortality in the world. Several studies show that most students do not have adequate food safety knowledge to protect themselves against foodborne diseases. This study aimed to determine the food safety knowledge, behaviour, and beliefs among undergraduate students at a local university in Malaysia. This cross-sectional study involves 121 respondents from three health science-related faculties at the studied institution. The questionnaire was distributed via an online platform. This study used multiple-choice-format questions for Food Safety Knowledge and a Likert type scale for Food Safety Behaviour and Belief question statements. Most of the respondents were female (78%). About 16% of the respondents have experience working /volunteering in food services, and half of them are involved in food handling during their services. This study recorded a moderate score in all sections (knowledge, behaviour, beliefs) with a total percentage score of 60.3%, 60.3%, and 66.1%, respectively. A strong but not significant correlation between food safety knowledge and beliefs (r = 0.69 p > 0.05) and between food safety knowledge and behaviour (r = 0.83 p > 0.05) were observed. This study is useful as a basis to develop a targeted food safety education program among undergraduate students. Students with high knowledge of food safety will increase food safety beliefs and behaviour, thus preventing them from getting any foodborne illness.